Parents' Challenges to Health Services for Children with Disabilities during the COVID-19 Pandemic: Literature Review - Nur Fadilah; Kadek Ayu Erika; Nur Azizah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Health services are important in supporting one's health. Due to social restrictions and regulations during a pandemic, access to health services also adapts to existing conditions. The purpose of this literature study is to identify challenges for parents in providing health services for children with disabilities during the COVID-19 pandemic. This research method used a literature review design using the PubMed, ProQuest, and ScienceDirect electronic databases. It was found that 7 articles were reviewed after fulfilling the inclusion criteria and were analysed. The results of the review found that a number of reasons for children with disabilities not participating in health services were due to several factors such as social restrictions, parents, and technology. Various relevant barriers to accessing health services are identified in this literature review. Challenges to social distancing were the most frequently reported in studies. The description in this study can be used as input in considering access and form of health services for children with disabilities.